Case report and systematic literature review of a novel etiology of sinistral portal hypertension presenting with UGI bleeding: Left gastric artery pseudoaneurysm compressing the splenic vein treated by embolization of the pseudoaneurysm. Issue 13 (March 2017) - Hakim, Seifeldin; Bortman, Jared; Orosey, Molly; Cappell, Mitchell S.
Abstract: Introduction: A novel case is reported of upper gastrointestinal (UGI) bleeding from sinistral portal hypertension, caused by a left gastric artery (LGA) pseudoaneurysm (PA) compressing the splenic vein (SV) that was successfully treated with PA embolization. Case report: A 41-year-old man with previous medical history of recurrent, alcoholic pancreatitis presented with several episodes of hematemesis and abdominal pain for 48 hours. Physical examination revealed a soft abdomen, with no abdominal bruit, no pulsatile abdominal mass, and no stigmata of chronic liver disease. The hemoglobin declined acutely from 12.3 to 9.3 g/dL. Biochemical parameters of liver function and routine coagulation profile were entirely within normal limits. Abdominal CT revealed a 5-cm-wide peripancreatic mass compressing the stomach and constricting the SV. Esophagogastroduodenoscopy showed blood oozing from portal hypertensive gastropathy, small nonbleeding gastric cardial and fundal varices, gastric compression from the extrinsic mass, and no esophageal varices. MRCP and angiography showed that the mass was vascular, arose from the LGA, compressed the mid SV without SV thrombosis, and caused sinistral portal hypertension. At angiography, the PA was angioembolized and occluded. The patient has been asymptomatic with no further bleeding and a stable hemoglobin level during 8 weeks of follow-up. Discussion: Literature review of the 14 reported cases of LGA PA revealed that this report of acute UGI bleeding from sinistral portal hypertension from a LGA PA constricting the SV is novel; one previously reported patient had severe anemia without acute UGI bleeding associated with sinistral portal hypertension from a LGA PA. Conclusion: A patient presented with UGI bleeding from sinistral portal hypertension from a LGA PA compressing the SV that was treated by angiographic obliteration of the PA which relieved the SV compression and arrested the UGI bleeding. Primary therapy for this syndrome should be addressed to obliterate the PA and not the secondarily constricted SV.